n-5=-9+3n

Simple and best practice solution for n-5=-9+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n-5=-9+3n equation:


Simplifying
n + -5 = -9 + 3n

Reorder the terms:
-5 + n = -9 + 3n

Solving
-5 + n = -9 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-5 + n + -3n = -9 + 3n + -3n

Combine like terms: n + -3n = -2n
-5 + -2n = -9 + 3n + -3n

Combine like terms: 3n + -3n = 0
-5 + -2n = -9 + 0
-5 + -2n = -9

Add '5' to each side of the equation.
-5 + 5 + -2n = -9 + 5

Combine like terms: -5 + 5 = 0
0 + -2n = -9 + 5
-2n = -9 + 5

Combine like terms: -9 + 5 = -4
-2n = -4

Divide each side by '-2'.
n = 2

Simplifying
n = 2

See similar equations:

| -4x-5(-x-9)=39 | | 2(y-5)-2x-y=7 | | 2X-3/4=-1/10 | | X=2x^2-5x+2 | | 13-4=6 | | 2(x-4)=3(x-1) | | 2a-4=10a | | 5a+3+6a-12+90=180 | | 11-5=5 | | .7(200-x)=126 | | 7(y+4)=3y-8 | | x+50=180 | | 8[4-(-4x-9)]=64x+176 | | .7(200-x)=133 | | solve(2+4)(2-2)=-5 | | 3(12-5)^2/(4+3) | | -2.1q-1=6.6 | | -4U+3/2=7/2U-1/5 | | 4+2x+15=x+13 | | 12x+25=29 | | 5a+3+6a-12=180 | | 4.7+3g=7.3 | | sqrt(5-x)+1=x-2 | | 4.2(x+8.7)=8.7x | | -4-n-4=-11 | | 6-x=37 | | 12x-1+3=7x+1 | | 3a/2+1=18 | | 22/5d*10/2 | | 3-4q=10+10 | | 3a+6+4a=-36 | | x+11=2x-7 |

Equations solver categories